A 150-year river water quality record shows reductions in phosphorus loads but not in algal growth potential - Helen P. Jarvie; Fred Worrall; Tim P. Burt; Nicholas J. K. Howden (Communications Earth & Environment, 2025)
Abstract Eutrophication and proliferation of nuisance and harmful algal blooms are a major cause of water-quality impairment globally. Here, we analyze the world’s longest continuous (150-year) river water-quality dataset for the River Thames, U.K. (including biological oxygen demand, chloride, phosphorus and silica), to explore the impacts of urbanization, wastewater discharges and agricultural intensification. Over the last 40 years, improvements in wastewater treatment and agricultural management have reduced phosphorus loads by ~80%. However, this has been insufficient to curtail river algal blooms because nutrient concentrations remain above limiting levels. Over the last 50–60 years, rising water temperatures have increased the number of days with water temperatures favourable for diatom blooms in March-April and for cyanobacterial growth in July-August. These results highlight the challenges of eutrophication management in a warming climate and a strategic need to redouble efforts in further reducing nutrient emissions to control nuisance and increasingly harmful algal blooms.